TINGKAT PENGELOLAAN IKAN TEMBANG (Sardinella gibbosa) YANG TERTANGKAP DENGAN BAGAN TANCAP DI KABUPATEN PANGKEP - Handayani Pratiwi B; Muhammad Jamal Alwi; Danial Danial (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2020)
The success of fishing depends on sufficient knowledge of the overall behavior of the fish, which is the basis for the development of existing methods. Utilization of Fishery Potential Activities in Pangkep Regency waters still depends a lot on simple fish catching technology. One of the factors for the success of catching fish with a chart is light. Light is a tool to help collect fish to the fishing area. Toli-toli village, Tekkolabua sub-district, Pangkep district is geographically located between 04º79'07.71 "- 4º79'14.35" LS and 119º43'75.13 "- 119º44'02.01" East Longitude (Figure 4). The administrative area is included in the North Liukang Tupabbiring District, Pangkep Regency. The production of tembang fish (S. gibbosa) caught with fixed-line fishing gear occurred in 2012 as much as 927.70 tons and the lowest was in 2009 as many as 50.30 tons. The level of utilization (TP) and level of cultivation (TPu) of fixed-line fisheries in Pangkep waters according to the Schaefer model for 8 years has exceeded the allowable utilization rate (JTB), namely in 2011, 2012, 2013, and in 2008, 2009 , 2010, 2014 and 2017 are still in an underexploited condition. Based on the analysis of the sustainable potential of tembang fish using the Schaefer model, the allowable amount of tembang fish catch (JTB) is 80% of the MSY value, it is recommended that the number of fish catches allowed in Pangkep Regency is 409.36 tons with a maximum number of fishing effort units of 26 units / year.